Pickering Emulsions: A Potential Strategy to Limiting Cancer Development - Singh, Sushil K.; Setia, Aseem; Singh, Shambhavi; Baghel, Yudhishthir Singh; Joshi, Deshbandhu; Bhattacharya, Sankha (Current Nanomedicine, 2022)
Pickering Emulsion therapy is a novel approach to treating various human diseases, including cancer. Traditional cancer treatment modalities, such as surgery, radiation, radiotherapy, and immunotherapy, have only achieved minimal success. Pickering emulsion in cancer therapeutics has given cancer patients a new hope. Pickering Emulsions have grown in popularity over the last 15 years, owing to their highly desirable properties, similar to those of ordinary emulsions, namely their excellent stability. This review focused on the benefits, drawbacks, characterization parameters (droplet size and strength, for example), opportunities, and different development procedures of Pickering Emulsion for cancer diseases. This review also addressed recent developments in Pickering Emulsions' technological issues. It examined the advantages and disadvantages of using such formulations for topical pharmaceutical and cosmetic applications instead of traditional surfactant-based methods. Pickering Emulsion's evolution as a multifunctional dosage form carrier reflects renewed optimism in the pharmaceutical and cosmetic industries.
Keywords: stability condition